FEM the Wood Revolution In-depth FE-analysis of a wood-glue-steel joint in a wind turbine tower - Borglund Aspler, Emil; Jern, Linnéa (My University, 2019)
Modvion is a company that develop 150m tall wind turbine towers made out of modules of Engineered Wood Products (EWP), specifically Laminated Veneer Lumber (LVL). One of the big challenges in their design is the joining of the modules, which is the focus of this thesis. The joint design was given from the beginning along with physical test data from tensile tests performed at Research Institutes of Sweden (RISE). In this thesis a Finite Element (FE)-model of the joint was created, with the aim to replicate the response obtained from the physical tensile tests using simulations. The main goal was to use the FE-model in order to describe the inner mechanics of the joint. The joining of two LVL panels is made with Loctite CR 421 Purbond and a perforated steel plate. The joint and its materials are studied using physical testing and the commercial softwares ANSA as pre-processor, Abaqus Unified FEA as solver, and META as postprocessor. The material parameters for the wood given by data sheets provided by the manufacturer are compared to physical test data. Remaining material parameters and simulation parameters are calibrated through material validation and parameter studies. Finally a small study was performed on whether the joint can be improved by making modifications to the perforated steel plate. The effects of these modifications were studied in order to find the critical areas of the joint. The obtained results show that the number of holes in the steel plate are critical for the performance of the joint when it comes to its tensile strength. This is because the holes enables the glue to create adhesive anchors that facilitates the stress transfer from the glue to the steel. Since the steel plate is the component of the joint that can withstand the highest amount of loading, the efficiency of the stress transfer is crucial in order to prevent the glue from breaking entirely at relatively small loads, which would result in a lower ultimate tensile strength of the joint. Although, some insecurities remains in the implementation of the FE-model, the results in this thesis can be used as a foundation for future research on this topic.
Keywords: Materialvetenskap; Produktion; Maskinteknik; Materialteknik; Materials Science; Production; Mechanical Engineering; Materials Engineering